A Cross-Sectional Cohort Study of Speech in Five-Year-Olds with Cleft Palate ± Lip to Support Development of National Audit Standards: Benchmarking Speech Standards in the United Kingdom. (July 2014) - Britton, Lorraine; Albery, Liz; Bowden, Melanie; Harding-Bell, Anne; Phippen, Ginette; Sell, Debbie
Objective: To develop national standards for speech outcomes and processes of care for children with cleft palate ± lip and to test the standards using national data. Design, Setting, and Participants: In this large, multicenter, prospective cohort study, speech recordings of 1110 five-year-olds with cleft palate involvement (born 2001 to 2003) were collected by 12 cleft centers in Great Britain and Ireland. Recordings were analyzed by consensus by specialist speech and language therapists using the Cleft Audit Protocol for Speech-Augmented. Results were benchmarked against evidence-based process and speech outcome standards and statistical analysis undertaken. Results: From the 1110 children audited, 48% (530) had speech within the normal range. This was not significantly different from the agreed standard of 50% ( P = .20, CI = 45–50%). Sixty-six percent (734) had speech with no evidence of structurally related speech problems or history of speech-related secondary surgery. This was significantly below the standard of 70% ( P =.007, CI = 62–69%). Sixty percent (666) had no serious cleft-related articulation errors. This was significantly better than the agreed standard of 50% ( P < .001, CI = 67–73%). More than 80% of 2-year-olds received a specialist speech and language assessment against a benchmark of 100%. Conclusions: Developing standards has facilitated more meaningful reporting of speech outcomes and treatment processes. Evidence-based standards were defined and extensively tested, enabling centers to compare their performance with national trends. One 5-year outcome standard was achievable; the other two standards will require modification through the mandatory annual national audit program.